2009
DOI: 10.1038/onc.2009.235
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like factor 5 promotes breast cell proliferation partially through upregulating the transcription of fibroblast growth factor binding protein 1

Abstract: The Kru¨ppel-like factor 5 (KLF5) is a zinc-finger transcription factor promoting cell proliferation, cellcycle progression and survival. A high expression level of KLF5 mRNA has been shown to be associated with shorter breast cancer patient survival. However, the mechanism of KLF5 action in breast cancer is still not clear. In this study, we found that both KLF5 and its downstream gene fibroblast growth factor binding protein 1 (FGF-BP) are co-expressed in breast cell lines and primary tumors. Manipulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
115
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(119 citation statements)
references
References 42 publications
4
115
0
Order By: Relevance
“…Higher KLF5 mRNA and protein expression is associated with a short survival time in breast cancer patients (33,34). Our previous studies demonstrated that KLF5 promotes MCF7 and HCC1937 breast cancer cell growth in vitro and in vivo (3,35). In this study, we showed several lines of evidence indicating that mPGES1 is a KLF5 direct target gene that partially mediates the pro-proliferative function of KLF5 in breast cancer cells.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Higher KLF5 mRNA and protein expression is associated with a short survival time in breast cancer patients (33,34). Our previous studies demonstrated that KLF5 promotes MCF7 and HCC1937 breast cancer cell growth in vitro and in vivo (3,35). In this study, we showed several lines of evidence indicating that mPGES1 is a KLF5 direct target gene that partially mediates the pro-proliferative function of KLF5 in breast cancer cells.…”
Section: Discussionmentioning
confidence: 55%
“…KLF5 expression can be induced by a variety of oncogenic and proinflammatory factors, such as LPS (38), TNF␣ (39), TPA (3,40), and so on. These proinflammatory stimuli also induce mPGES1 (10,17,41).…”
Section: Discussionmentioning
confidence: 99%
“…breast cell lines (17). The KLF5 E3 ligase WWP1 is overexpressed in ERα-positive breast cancer (28).…”
Section: The Expression Of Fbw7 and Klf5 In Breast Cancermentioning
confidence: 99%
“…KLF5 is highly expressed in estrogen receptor (ER)α-negative basal-type breast cancer and is an unfavorable prognostic biomarker correlated with shorter survival for breast cancer patients (18,19). Our previous studies suggest that KLF5 promotes breast cell proliferation through directly upregulating the FGF-BP gene transcription (17). More recently, inhibition of KLF5 by small interfering RNA (siRNA) using nanoparticles has been shown to efficiently inhibit tumor growth in vivo (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation